Preoperative study of the inner segment/outer segment junction of photoreceptors by spectral-domain optical coherence tomography as a prognostic factor in patients with epiretinal membranes - Cobos E (Dove Medical Press, 2013)
E Cobos,1 L Arias,1 JM Ruiz-Moreno,2,3 MJ Rubio,1 P Garcia-Bru,1 JM Caminal,1 J Catala,1 J Arruga11Department of Ophthalmology, Bellvitge University Hospital, Barcelona, Spain; 2Department of Ophthalmology, Castilla La Mancha University, Albacete, Spain; 3Alicante Institute of Ophthalmology, VISSUM, Vitreo-Retinal Unit, Alicante, SpainObjective: To demonstrate whether the preoperative integrity of the inner segment/outer segment (IS/OS) junction of photoreceptors studied by spectral-domain optical coherence tomography (SD-OCT) is a prognostic factor in epiretinal membrane surgery.Methods: We retrospectively studied patients with an idiopathic epiretinal membrane who underwent a 23-gauge vitrectomy to remove this membrane. Best-corrected visual acuity (BCVA) and SD-OCT scans were examined before and 6 months after the surgery. We studied the retinal microstructure, especially the IS/OS junction of the photoreceptors, and evaluated the intergroup differences between patients with an intact layer and those with an irregular or disrupted layer. We applied both the Wilcoxon and Mann–Whitney tests for statistical analysis.Results: In total, 51 eyes from 51 enrolled patients were examined in this study. The postoperative BCVA was significantly better for eyes that had an intact IS/OS junction than for eyes that had an irregular or disrupted IS/OS junction, as preoperatively observed with SD-OCT scans (P < 0.001). We also observed an important association between disrupted IS/OS junctions and the presence of cystic macular edema (P < 0.01).Conclusion: The presence of an intact IS/OS junction on the preoperative SD-OCT scan was an important predictor of better visual recovery after epiretinal membrane surgery. Keywords: epiretinal membrane, photoreceptors, inner segment/outer segment junction, spectral-domain optical coherence tomography